Communicating climate change in Portugal: a critical analysis of journalism and beyond - Carvalho, Anabela (2008)
This chapter analyses discourses circulating in the Portuguese public sphere(s) about climate change, and discusses the problems associated with representations of the issue in the press and television news. Understandings of risk and responsibility are given particular emphasis given their importance for problem definition and proposed courses of action. The study covers four print media: Correio da Manhã (a popular daily newspaper), Expresso (a quality weekly newspaper), Público (a quality daily newspaper) and Visão (a mid-market weekly news magazine). Various aspects of press coverage since 1990 are examined but we focus in more detail on four ‘critical moments’ between 2003 and 2007. A sample of recent television news from RTP1, 2: (both part of the public broadcasting company), SIC and TVI (private channels) is also analysed. Besides journalistic discourse, we look at some aspects of the communication of climate change by politicians, non-governmental organizations and other social actors, and how it relates to media discourses.